Strategic Human Resource Management Practices and Organizational Effectiveness in the Lake Region Counties, Kenya - Omollo, Vivian; Juma, Dennis (Journal of Business and Strategic Management, 2025)
Purpose: This study investigated the effect of strategic human resource management (SHRM) practices on organizational effectiveness in the Lake Region counties of Kenya. The study specifically examined strategic performance management, strategic employee development, strategic motivation, and strategic talent management as key predictors of organizational effectiveness. Methodology: A descriptive survey design was employed, integrating both qualitative and quantitative research methods to ensure a comprehensive analysis. The study targeted HR managers and supervisors in county governments across the Lake Region, employing stratified random sampling to ensure fair representation from different departments. Primary data was collected using structured questionnaires, with reliability and validity tested through Cronbach’s Alpha and factor analysis, respectively. Data analysis was conducted using descriptive and inferential statistics, including correlation and regression analysis. Correlation and regression analyses were conducted using data from 105 respondents. Findings: The results revealed that all four SHRM practices had significant positive relationships with organizational effectiveness. Strategic motivation mechanisms had the strongest effect, followed by employee development, performance management, and talent management. These findings suggest that counties that invest in employee recognition, continuous training, structured performance systems, and talent pipelines experience improved operational efficiency and service delivery. Unique Contributions to Theory, Practice and Policy: The study highlights the value of aligning HR strategies with county goals, while recommendations emphasize the need for HR policy frameworks that support motivation, training, and succession planning. The study suggests further research on mediating factors such as organizational culture, and advocates for longitudinal and regionally comparative studies. It also proposes incorporating employee perspectives and examining the role of technology in HRM. Overall, the study provides evidence that effective strategic HRM practices are essential drivers of performance and can enhance the capacity of devolved governments in Kenya to deliver quality services.